Soil moisture monitoring using field programmable gate array - Husni, Muhammed Ihsan; Hussein, Mohammed Kareem; Zainal, Mohd Shamian; Hamzah, Shipun Anuar; Md Nor, Danial; Mhd Poad, Hazwaj (Institute of Advanced Engineering and Science (IAES), 2018)
This paper presents a solution for remote monitoring and sensing of different agricultural parameters that effect the plant growth and productivity. Hardware descriptive language has been used for the implementation of proposed topology on Field Programmable Gate Arrays. The hardware used for this purpose is an Altera board. The simulated results take into consideration the environmental factors such as the humidity, soil moisture content and the temperature. The proposed system continuously monitors the environmental changes for any updates. The system also controls a water motor that is turned on as the system senses the reduction in moisture content. The system implementation on hard wave level show promising results and have been discussed in detailed.